PENGARUH GAYA HIDUP DAN LITERASI KEUANGAN TERHADAPA KEPUTUSAN BERINVESTASI GENERASI MILINIAL KOTA TANGERANG SELATAN - Arman Syah; Akhmar Barsah (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The main problem in this research is related to the influence of lifestyle and financial literacy on the decision to invest in the millennial generation in South Tangerang City. The purpose of this research is the first to find out partially the influence of lifestyle on the millennial generation's investment decisions in South Tangerang City. The second is to find out partially the effect of financial literacy on the millennial generation's investment decisions in South Tangerang City. The third is to determine the simultaneous influence of lifestyle and financial literacy on the millennial generation's investment decisions in South Tangerang City. The research method used is based on a quantitative type classification with an associative (causal) form. Based on the tests and analyzes that have been carried out in the regression model, the results of the multiple correlation coefficient of 0.605 are included in the strong category, while the value of Adjusted R square as the contribution of the independent variables to the dependent variable is 0.363 or 36.3% where 63.7% is the contribution of other factors not studied. The proof of the partial significance test shows that lifestyle results have a significant effect on investment decisions with a tcount > ttable (7.627 > 1.64), while the effect of financial literacy on investment decisions is obtained by a tcount > ttable (9,962 > 1.64) and it is proven that there is an effect significant. Simultaneous influence of lifestyle and financial literacy on investment decisions there is a significant influence where the value of Fcount > Ftable (114.455 > 2.31).